The Communication Skills Assessment Instrument Development for Mild Intellectual Disability Children in Special Needs School - Andana, Ollivia Dinda; Fathonah, Siti; Ahmadi, Farid (Journal of English Language and Education, 2025)
This research talked about assessment instrument development which had purpose to assess the communication skills of mild intellectual disability children. Intellectual disability children are a special needs children who has restricted capability in their intellectual so that they are difficult to do daily activities such as: caring, taking care themselves, communicating, and using money. After doing an interview with the teachers of SLB BC Autis YBA Surakarta, it could be found that there isn’t an assessment to assess the communication skills for mild intellectual disability children. The teachers told that they only had  an assessment instrument for their individual needs in order to help them independent when they aren’t with their parents. Whereas the communication skills is important because it is used to tell about desire and maintain the good relationship with surroundings. This research was a research development that using 3D design (define, design, develop). This development research made 15 statement points that used to assess the communication skills of mild intellectual disability children which had results as follow: (1) validity test got a result 0,97 that was declared as valid; (2) reliability test for subjects outside the small-scale subjects with a result 0,90 and for the small-scale subjects with a result 0,87; (3) practicallity test for the subjects outside the small-scale subject with a result 98% and for the small-scale subject with a result 88% that was categorized as very practical.